Analisis Tindak Tutur Ekspresif pada Film Kukira Kau Rumah Karya Umay Shahab - Ananda Dwi Rahayu; Kafita Widyawati; Carissa Permata Putri; Meisya Nadia Diana; Naurah Nadzifah Ramadhani; Asep Purwo Yudi Utomo; Ermawati. S; Turahmat Turahmat (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language has a crucial role in understanding human communication, one of which is through speech actions carried out by humans. The existence of speech acts is so diverse, one of which is expressive speech that can reflect the psychological condition of the speaker. This research chose the film Kukira Kau Rumah as an object, because film is one of the objects that contains speech acts through dialogue. In the film, there are many dialogues that are emotionally charged and relevant to mental health issues. The study of this film is important because it can provide a new perspective in pragmatics, especially understanding how language is used to express emotions, build character dynamics, and represent the form of expressive speech itself. This study uses a descriptive qualitative method whose analysis is carried out on the dialogues in the film to find various expressive speech acts, identify the types of expressive speech acts, and define the meaning of speech acts to the context related to these speech acts. The types of expressive speech that were found included the expressive act of praise, thanks, criticism, complaining, blaming, congratulating, and apologizing. This research is expected to contribute new insights in pragmatic studies, especially regarding the analysis of expressive speech acts and new references for linguistic studies.